Time variation of the electron mass in the early universe and the Barrow-Magueijo model - Scóccola, Claudia Graciela (2008)
We put limits on the time variation of the electron mass in the early universe using observational primordial abundances of D, 4He, and 7Li, recent data from the cosmic microwave background, and the 2dFGRS power spectrum. Furthermore, we use these constraints together with other astronomical and geophysical bounds from the late universe to test the Barrow-Magueijo model for the variation in me. From our analysis we obtain -0.615 < Gω/c4 < -0.045 (3 σ interval), in disagreement with the result obtained in the original paper.